Extending switching frequency for torque ripple reduction utilizing a constant frequency torque controller in DTC of induction motors - Jidin, Auzani; Elbuluk, Malik E.; Sutikno, Tole; Nik Idris, Nik Rumzi; Mohamed Yatim, Abdul Halim (Korean Institute of Power Electronics, 2011)
Direct torque control (DTC) of induction machines is known to offer fast instantaneous torque and flux control with a simple control structure. However, this scheme has two major disadvantageous, namely, a variable inverter switching frequency and a high torque ripple. These problems occur due to the use of hysteresis comparators in conventional DTC schemes, particularly in controlling the output torque. This paper reviews the utilization of constant frequency torque controllers (CFTC) in DTC to solve these problems while retaining the simple control structure of DTC. Some extensions of the work in utilizing a CFTC will be carried out in this paper which can further reduce the torque ripple. This is particularly useful for a system which has a limited/low sampling frequency. The feasibility of a CFTC with an extended carrier frequency in minimizing the torque ripple is verified through experimental results.